A low power, low noise figure quadrature demodulator for a 60 GHz receiver in 65-nm CMOS technology*Project supported by the National High Technology Research and Development Program of China (No. 2011AA010200). (April 2015) - Amin, Najam Muhammad; Wang, Zhigong; Li, Zhiqun; Li, Qin; Liu, Yang
Abstract This paper presents the design of a low power (LP) and a low noise figure (NF) quadrature demodulator with an on-chip frequency divider for quadrature local oscillator (LO) signal generation. The transconductance stage of the mixer is implemented by an AC-coupled self-bias current reuse topology. On-chip series inductors are employed at the gate terminals of the differential input transconductance stage to improve the voltage gain by enhancing the effective transconductance. The chip is implemented in 65-nm LP CMOS technology. The demodulator is designed for an input radio frequency (RF) band ranging from 10.25 to 13.75 GHz. A fixed LO frequency of 12 GHz down-converts the RF band to an intermediate frequency (IF) band ranging from DC to 1.75 GHz. From 10 MHz to 1.75 GHz the demodulator achieves a voltage conversion gain (VCG) ranging from 14.2 to 13.2 dB, and a minimum single-sideband NF (SSB-NF) of 9 dB. The measured third-order input intercept point (IIP3) is −3.3 dBm for a two-tone test frequency spacing of 1 MHz. The mixer alone draws a current of only 2.5 mA, whereas the complete demodulator draws a current of 7.18 mA from a 1.2 V supply. The measurement results for a frequency divider, which was fabricated individually, prior to being integrated with the quadrature demodulator, in 65-nm LP CMOS technology, are also presented in this paper.